Testosterone Is Associated with Erectile Dysfunction: A Cross-Sectional Study in Chinese Men - Liao, Ming; Huang, Xianghua; Gao, Yong; Tan, Aihua; Lu, Zheng; Wu, Chunlei; Zhang, Youjie; Yang, Xiaobo; Zhang, Haiying; Qin, Xue; Mo, Zengnan (PLOS ONE, 2012)
Background Testosterone is essential for the regulation of erectile physiology, but the relationship between low testosterone and erectile dysfunction (ED) has not been firmly established. Purpose To examine the association between serum total, free and bio-available testosterone and ED in a population-based sample. Methods A consecutive series of 1776 men aged 20–77 participated in the routine physical examination from September 2009 to December 2009 in Guangxi, China. ED was assessed using the five-item International Index of Erectile Function (IIEF-5) questionnaire. Total testosterone (TT), sex hormone binding globulin (SHBG) and other biochemical profiles were measured. Free testosterone (FT) and bio-available testosterone (BT) were calculated based on Vermeulen’s formula. Data were collected with regard to smoking, alcoholic drinking, physical activity and metabolic syndrome. Results The prevalence of ED (IIEF-5<22) was 47.6%. Men with ED were significantly older, and more prone to smoke cigarettes (≥20 cigarettes/day) or drink alcohol (≥3 drinks/week), and more likely to have elevated blood pressure (P = 0.036) or hyperglycemia (P<0.001) compared with those without ED. The significant increase in SHBG with age was parallel to its increase with increasing severity of ED (P<0.001). The obscure increase in TT across the ED status was detected without significance (P = 0.418), but TT was positively associated with ED after adjustment for age [odds ratio (OR) = 1.02, 95% CI (confidence internal): 1.00–1.04]. FT and BT were inversely associated with ED (OR = 0.14, 95%CI: 0.06–0.33; OR = 0.92 (95%CI: 0.89–0.96, respectively) in the univariate analysis, and this inverse association appeared to be independent of smoking status, alcoholic drinking, physical activity, hyper-triglyceridemia and hyperglycemia. Conclusions FT and BT are inversely related to worsening ED, whereas the positive association between TT and ED is most likely due to the increase in SHBG.